2020
DOI: 10.3390/ijerph17103595
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Burnout Syndrome in Primary and Secondary School Teachers in the Republic of Srpska (Bosnia and Herzegovina)

Abstract: Objectives: The aim of this study was to estimate the prevalence of burnout syndrome in a large sample of primary and secondary school teachers in the Republic of Srpska (Bosnia and Herzegovina) and identify the factors associated with burnout in this population. Methods: This cross-sectional study was conducted in August and September of 2018, on a sample of 952 teachers. Beside socio-demographic information, Bortner scale, Job Content Questionnaire, and Maslach Burnout Inventory were filled in by the study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 39 publications
2
22
1
1
Order By: Relevance
“…Consequently, it represents a significant public health problem. Marić et al have suggested development of regular screening programs for burnout syndrome, which could be implemented before the beginning, in the middle and at the end of the school year (45). Further research is inevitable in order to better understand this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it represents a significant public health problem. Marić et al have suggested development of regular screening programs for burnout syndrome, which could be implemented before the beginning, in the middle and at the end of the school year (45). Further research is inevitable in order to better understand this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…High level of emotional exhaustion was mainly reported by teachers belonging to the region of East Sarajevo and Prijedor (Figure 2). In the research conducted in the Republic of Srpska, concerning the factors that influence the development of burnout syndrome at work among teachers, 24 conflicts of roles and satisfaction with the support of family and friends proved to be one of the important factors. Bearing in mind teachers from the Prijedor region had conflict roles much more often and were more dissatisfied with the support, that can explain the reason for the much more frequent emotional exhaustion in this region.…”
Section: Emotional Exhaustion Depersonalisationmentioning
confidence: 99%
“…Also, teachers from this region who participated in the research were mostly teachers older than 45 years (Table 1) and had more years of work experience (Table 2) which can also be an explanation for the more frequent manifestation of emotional exhaustion. Other authors 21,24,25 also pointed out that older teachers more often report emotional exhaustion, explaining that with age, it is more and more difficult to face student's problems on daily basis. Teachers from the territory of the Prijedor region more often showed a moderate and high level of depersonalization (Figure 3), so as a low level of personal achievement (Figure 4) comparing to teachers who belong to other regions.…”
Section: Emotional Exhaustion Depersonalisationmentioning
confidence: 99%
“…Burnout syndrome is in some European countries recognized as an occupational disease. Burnout syndrome has been earlier identified predominantly in the service sectors such as healthcare, social services, mental health and education, but later it started to be predominant in other occupations with high job requirements and time pressure (e.g., managers) like bank employees (8,9). According to the European Foundation for the Improvement of Living and Working Conditions (Eurofound) stress is one of the major occupational problems in banking sector (10).…”
Section: Introductionmentioning
confidence: 99%